2008
DOI: 10.14453/aabfj.v2i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Accounting and accountability by provincial councils in Fiji: the case of Namosi

Abstract: The aim of this paper is twofold: firstly to examine how the concepts of accounting and accountability are understood by indigenous Fijians; and secondly to examine the role of accounting in the accountability of provincial councils. Provincial councils are part of the Fijian Administration, which runs alongside the central government but applies only to indigenous Fijians. The Fijian Administration was introduced by the British colonial administration in the late 1800s as a mechanism for controlling indigenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…An Eastern chief began to rule the country again. A national body called the council of chiefs was established at the apex of the indigenous Fijian administration (Rika et al, 2008). This ensured that chiefs retained political control of the country.…”
Section: Accounting and Accountability In An Old Government Department (1970–1989) Within Its Wider Cultural And Political Contextmentioning
confidence: 99%
“…An Eastern chief began to rule the country again. A national body called the council of chiefs was established at the apex of the indigenous Fijian administration (Rika et al, 2008). This ensured that chiefs retained political control of the country.…”
Section: Accounting and Accountability In An Old Government Department (1970–1989) Within Its Wider Cultural And Political Contextmentioning
confidence: 99%
“…Rika et al. () examine how accounting and accountability concepts are understood by indigenous Fijians. Rika et al.…”
Section: Taking Stock Of Acquired Knowledgementioning
confidence: 99%
“…Rika et al. () found that indigenous Fijians identified several meanings and words in relation to the term ‘accountability’ but no consistent terminology was used. Rika et al.…”
Section: Taking Stock Of Acquired Knowledgementioning
confidence: 99%
“…Therefore the more implicit criticism may be that the British did not use their power to reform what could be regarded as an inherently unjust society. This perceived injustice included a focus on upward accountability, with less emphasis on downward accountability (Davie, 2005b; Rika et al, 2008).…”
Section: Background and Context To Rugby And Fijimentioning
confidence: 99%